Performing Embodiable Topoi: Strategic Indigeneity and the Incorporation of Ecuadorian National Identity - Olson, Christa J. (The Quarterly journal of speech, 2010)
The rhetorical history of Ecuador is rife with examples of politicians, intellectuals, and artists promoting visions of national identity through images of Ecuador's indigenous population. Between the late nineteenth and mid-twentieth centuries, such depictions became common and displayed increasing emphasis on the physical characteristics of indigenous people. This focus led to appropriations of indigeneity in which white and mestizo Ecuadorians spoke as if indigenous in order to construct arguments about their place in the nation. In the process, they engaged an "embodiable topos" that housed persuasive force within bodily performances of indigenous character. White-mestizo performances of indigeneity engaged embodiable topoi in order to appropriate specific positions associated with indigenous subjects and to establish access to otherwise unavailable forms of rhetorical legitimacy.